Perilaku Petani dalam Budidaya Tanaman Kakao (Subak-Abian Asagan di Kecamatan Selemadeg Timur Kabupaten Tabanan) - JAYA, MARSELINA SUNARTI; PUTRA, I GEDE SETIAWAN ADI; SARJANA, I MADE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.1, Juli 2023, 2023)
Farmers Behavior in Cultivating Subak-Abian Asagan Cocoa Crops ( in Selemadeg Timur District, Tabanan Regency ) Agriculture is a sector that plays an important role in building the national economy. Knowing the attitude of farmers in cacao cultivation in Subak Abian Asagan, Gadungan Village, East Selemadeg District. Knowing the skills of farmers in cacao cultivation in Subak Abian Asagan, Gadungan Village, East Selemadeg District. This research was conducted in Subak Abian Asagan, Gadungan Village, East Selemadeg District, Tabanan Regency. The location of this study was chosen by purposive sampling or intentionally, carried out from April to May 2021, the sample in this study was determined by the random sampling method, where the total population was 60 with a sample of 38 cocoa farmers. Subak Abian Asagan, Gadungan Village, Selemadeg Timur, Tabanan Regency already has knowledge that is classified as high category in terms of cacao cultivation. Subak Abian Asagan, Gadungan Village, Selemadeg Timur, Tabanan Regency already has an attitude that is classified as very good in terms of cacao cultivation. Based on the results of the research and the conclusions above, the following suggestions can be given: The knowledge of Subak Abian Asagan, East Gadungan Village, Tabanan Regency continues to be improved, especially regarding paying attention to soil texture in the cocoa cultivation process and ideal cocoa spacing, as well as disease management. rotten fruit that can inhibit the growth of cocoa plants. The attitude of members of Subak Abian Asagan, Gadungan Village, Selemadeg Timur, Tabanan Regency needs to be improved again with attitudes about differences.